Word formation and inflection of non-substantive lexico-grammatical classes in the ancient Turkic language - Dubrovina Маргарита (Turkic Studies Journal, 2024)
In this article, the author turns to the material of the first written language of the Turks, namely the language of ancient Turkic runic inscriptions. The monuments date from the period between the 6th and 9th centuries and consist of texts carved on stone surfaces using specific runic signs. This language is of interest from a number of perspectives, but this study focuses on the morphology of parts of speech that are rarely discussed in specialized Turkic literature, namely adjectives, adverbs and numerals. A comprehensive examination of the language in question reveals that, despite its ancient origins, it has already developed a sophisticated system of word formation for non-substantive categories. Adjectives can be formed using a variety of forms, and adverbs have at least one word formation form. The sphere of inflection (formation) also begins to emerge; in the language of this period, it primarily affects numerals, which possess both ordinal and collective forms. The author refers to the latter forms under inflection rather than word formation due to the fact that the newly formed numeral forms do not change their original lexical meaning, continuing to express specific quantities.